ANALISIS STUDI KELAYAKAN BISNIS SYARIAH PADA USAHA MIKRO PEMBUATAN TEMPE (Studi pada Desa Palak Siring Kecamatan Kedurang) - Hardi, Namang Juki; Isnaini, Desi; Nurhab, Muhammad Irpan (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the feasibility of sharia-based business practices in micro enterprises producing tempeh in Palak Siring Village, Kedurang District. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving 12 informants, including the owner, employees, marketing staff, and consumers. The results show that in terms of financial aspects, the business is not yet fully feasible as there is no structured financial recording, and business finances are mixed with personal finances. In marketing, the business is fairly feasible with the implementation of honesty and trustworthiness values, although promotion is still conventional. Meanwhile, in the production aspect, the business is considered feasible, using halal raw materials, hygienic processes, and environmentally friendly waste management. Overall, the tempeh micro-enterprise has good potential for development in line with sharia economic principles, especially with proper managerial support and access to sharia-compliant financing.